Medinfo 2004: Proceedings of the 11th World Congress on MedicalIinformatics - Coiera, Enrico (IOS, 2013)
A fundamental challenge for medical informatics is to develop and apply better ways of understanding how information technologies and methods can help support the best care for every patient every day given available medical knowledge and resources. In order to provide the most effective healthcare possible, the activities of teams of health professionals have to be coordinated through well-designed processes centered on the needs of patients. For information systems to be accepted and used in such an environment, they must balance standardization based on shared medical knowledge with the flexibility required for customization to the individual patient. Developing innovative approaches to design and build evidence-based careflow management systems is essential for providing the knowledge management infrastructure of healthcare organizations that seek to increase performance in delivering high quality care services by efficiently exploiting available resources. Parallel challenges arise in the organization of research at the biological and clinical levels, where the focus on systematically organizing and supporting processes of scientific inquiry by novel informatics methods and databases are in their very early stages. These Proceedings of Medinfo 2004 demonstrate the base of knowledge medical informatics professionals will collectively draw upon in the years ahead to meet these challenges and realize opportunities.